Capital Flows, Financial Asset Prices and Real Financial Market Exchange Rate: A Case Study for an Emerging Market, India - Ghosh, Saurabh; Reitz, Stefan (Journal of Reviews on Global Economics, 2013)
Abstract: In this paper we empirically investigate the relationship between capital flows and exchange rates in India based on a new index of real effective exchange rates for the Indian Rupee. Instead of using consumer price indices we deflate exchange rates by MSCI asset price indices. The cointegration analysis indicates a long-run equilibrium relationship between real financial market exchange rate and the net outstanding equity investment in India. In the short run capital inflows are accompanied by an appreciation of real financial exchange rate of the Rupee.